'His Life Rose With Him'—John 21 and the Resurrection of Jesus. (May 2019) - O'Collins, Gerald
The history of Jesus as portrayed in the Fourth Gospel, not least his relationship with Peter and the Beloved Disciple and his role as light and life of the world, rose with him in the final Easter episode (Ch. 21). The questioning style of Jesus and the love exhibited and commanded by him also rose again in that resurrection narrative. Further themes from the history of Jesus, such as meals, the Eucharist, martyrdom, testimony, and truth, also find their place in the account of the risen Jesus.